THE USE OF ZX27 BIO-GLASS ABUTMENTS IN BITERMINAL EDENTATIONS TO SOLVE PROBLEMS OF MASTICATION AND PHYSIOGNOMY - Mitrea Mihaela; Sintea Cristina; Calin Dorelia Lucia; Francu LL (Romanian Society of Oral Rehabilitation, 2013)
International experience shows that ZX-27 bio-glass pillar or abutment can handle more difficult cases, usually biterminal edentation when, for various reasons, skeletal and/or telescope prostheses or implants cannot be made and works very well. The authors present their experience in using this innovative material that adapts perfectly to each patient, while providing optimal functional and aesthetic results through a technique with reduced costs and execution time.